Open Access GNSS Data for Studies of the Lithosphere - D. Sarah Stamps; Corné Kreemer (Geochemistry, Geophysics, Geosystems)
Abstract Various types of Global Navigation Satellite System (GNSS) data are used for a wide range of applications. When modeled correctly, millimeter precision daily GNSS position time‐series yield velocities and other derived products that can be used for investigations of lithospheric processes and properties. In this review paper, we describe the specific types of GNSS data and data products that are valuable for studies of the lithosphere, such as coseismic offsets, post‐seismic decay in time‐series, seasonal signals, secular velocities, and strain rates, and how those data are derived. We also discuss the applications of several types of GNSS data and data products. We provide open access resources for precision GNSS daily position time‐series, quality secular velocity solutions, and daily GNSS RINEX files for researchers interested in processing their own data.